A fair arbitration for Network-on-Chip routing with odd-even turn model. (June 2017) - Liu, Lu; Zhu, Zhangming; Zhou, Duan; Yang, Yintang
Abstract: With the increasing of Network-on-Chip size, deterministic routing algorithms suffer from a poor performance under heavy traffic. Therefore, routing schemes with varied candidate paths and fair selection strategy are required to relieve congestion. We propose an alterable priority arbitration for the fair granting of packet transmission from all possible directions permitted by the odd-even turn model. To achieve fairness, the proposed arbitration strategy alters the priority orders based on an optimized pointer, its granting decisions are made according to fixed mechanism under varied priority orders. Under a cycle-accurate simulator based on System C, the proposed alterable priority arbiter is verified to achieve better fairness than the RR arbiter. Simulation results show that the average packet latency of the odd-even turn model is reduced by 26.46%, and the saturation throughput is improved by 29.79% with the introduction of proposed arbitration scheme. Furthermore, the proposed arbiter achieves ignorable increasing of the hardware implementation overhead.